Тhe dissemination of the innovative experience as a factor of the modernization of pedagogical education - Yulia V. Vardanyan (Высшее образование в России)
The article is devoted to the characteristic of the possibility of the university research and education complex to promote the innovative experience of teachers and ensure itsdissemination. The increasing influence of this university infrastructure on the process ofmodernization of the system of training, retraining and advanced training of pedagogical staff is analyzed. The main goal of the centre is to involve teachers into the process of study, development and application of new effective approaches in their pedagogical activities.